2006
DOI: 10.1111/j.1526-100x.2006.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Complex Effects of Prescribed Fire on Restoring the Soil Water Content in a High‐Elevation Riparian Meadow, Arizona

Abstract: One of the largest and rarest Bebb willow (Salix bebbiana) communities in the United States occurs at Hart Prairie, Arizona. Low recruitment of the willow over the past several decades has been linked to inadequate soil water content for seed germination and seedling establishment. We tested a hypothesis that a prescribed burn would reduce biomass of and evapotranspiration by herbaceous plants, thereby increasing soil water content. Three treatments (unburned control, early-growing season burned, late-growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Silberstein et al () demonstrated that forest sites affected by fire tend to show significant increase in soil moisture storage due to reduced leaf area relative to the unburnt sites and the associated reduction in ET from vegetation. Another study (Mullen, Springer, & Kolb, ) demonstrates that climate variations, such as very wet or dry periods after the fire, complicate the use of fire as a tool for enhancing groundwater recharge. Precipitation in the post‐fire period (2013–2016) is 16% larger than the average annual value (1976–2016).…”
Section: Resultsmentioning
confidence: 99%
“…Silberstein et al () demonstrated that forest sites affected by fire tend to show significant increase in soil moisture storage due to reduced leaf area relative to the unburnt sites and the associated reduction in ET from vegetation. Another study (Mullen, Springer, & Kolb, ) demonstrates that climate variations, such as very wet or dry periods after the fire, complicate the use of fire as a tool for enhancing groundwater recharge. Precipitation in the post‐fire period (2013–2016) is 16% larger than the average annual value (1976–2016).…”
Section: Resultsmentioning
confidence: 99%
“…Burning changed soil temperature and soil moisture greatly in the present study (Figure 1). When a fire scorches a large fraction of the aboveground canopy, evapotranspiration is reduced greatly (Beringer et al 2003; Mullen et al 2006). Therefore, transient higher soil moisture was observed on 25 June (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In the middle and late growing season, when plants need to uptake more water from the soil, and ecosystem evapotranspiration was higher due to the high temperature, burning‐induced decrease in soil moisture (Figure 1A) might have aggravated water limitation on plant growth. The negative effect of burning caused by lower soil moisture might counteract the positive effect that resulted from the increases in nutrient availability (Mack et al 2001; Wan et al 2001) or the higher radiation (Mullen et al 2006). Over the whole growing season, the burning‐induced changes in monthly mean soil moisture could explain 51% ( P < 0.001) of the burning‐induced changes in P n of all three species (Figure 7A), suggesting that burning‐induced soil moisture was the main driving factor for plant photosynthetic responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil moisture pulses appear to last ¾5 days after which values return to pre-storm levels, suggesting that soil moisture persists in the surface layer despite losses to infiltration, evapotranspiration and downslope redistribution (e.g. Mullen et al, 2006). A comparison of the soil moisture amount and its variability at the four transects can provide an indication of the differences in hydrologic response across the grassland to forest transition.…”
Section: Spatial and Temporal Variability In Soil Moisturementioning
confidence: 99%